PENGARUH TRUST CORPORATE DAN MARKETING COMMUNICATION TERHADAP CUSTOMER SATISFACTION PADA PERUSAHAAN JASA PT AAJI MANULIFE SURABAYA - jannah, Nur (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2019)
This study aims to determine the effect of corpoarate trust and marketing communication on customer satisfaction on PT. AAJI Insurance Manulife Surabaya. This type of research is survey research that uses or has used insurance services at PT.AAJI Manulife Surabaya. The sampling technique accidental sampling, so that the number of samples obtained is 100 people. The technique of collecting data uses questionnaires and tabulations that have been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results of this study found that there is a simultaneous influence of corporate and communication trust on customer satisfaction and empirically the partial effect that corporate trust has a positive and significant effect on customer satisfaction and marketing communication has a positive and significant effect on customer satisfaction. Keywords: Corporate trust, Marketing Communication, Customer Satisfaction